Analisis Faktor Produksi Dan Kapasitas Layanan Terhadap Kinerja Pendapatan Jasa Di PT Multi Terminal Indonesia - Nurfahira, Aisyah; Widhiatmoko, Bimo; Pratiwi, Sekar Widyastuti (Institut Transportasi dan Logistik Trisakti, 2025)
PT Multi Terminal Indonesia is a company engaged in the logistics sector, which has several logistics services ranging from cargo handling, storage, transportation to distribution of goods. This study aims to determine and analyze the effect of production and service capacity on PT Multi Terminal Indonesia's service revenue performance in 2022. This research method uses a quantitative approach by conducting several tests, namely the classical assumption test, multiple linear regression tests and hypothesis testing. The research results show that production and service capacity have a significant effect on PT Multi Terminal Indonesia's service revenue. In this case, production and service capacity can increase PT Multi Terminal Indonesia's revenue if used optimally. Service capacity contributes the most to service revenue compared to production.